In vivo proximity biotin ligation identifies the interactome of Egalitarian, a Dynein cargo adaptor. - Baker, F.C.; Neiswender, H.; Veeranan-Karmegam, R.; Gonsalvez, G.B. (Development, 2021)
Numerous motors of the Kinesin family contribute to plus-end-directed microtubule transport. However, almost all transport towards the minus-end of microtubules involves Dynein. Understanding the mechanism by which Dynein transports this vast diversity of cargo is the focus of intense research. In selected cases, adaptors that link a particular cargo with Dynein have been identified. However, the sheer diversity of cargo suggests that additional adaptors must exist. We used the Drosophila egg chamber as a model to address this issue. Within egg chambers, Egalitarian is required for linking mRNA with Dynein. However, in the absence of Egalitarian, Dynein transport into the oocyte is severely compromised. This suggests that additional cargoes might be linked to Dynein in an Egalitarian-dependent manner. We therefore used proximity biotin ligation to define the interactome of Egalitarian. This approach yielded several novel interacting partners, including P body components and proteins that associate with Dynein in mammalian cells. We also devised and validated a nanobody-based proximity biotinylation strategy that can be used to define the interactome of any GFP-tagged protein.